Green value stream mapping approach to improving productivity and environmental performance. Issue 3 (4th March 2019) - Muñoz-Villamizar, Andrés; Santos, Javier; Garcia-Sabater, Julio J.; Lleo, Alvaro; Grau, Paloma
Abstract : Purpose: The purpose of this paper is to introduce a new methodology called overall greenness performance for value stream mapping (OGP-VSM). Using value-added concepts, this approach has the potential to integrate, measure, control and improve productive and environmental performance in accordance with a company's context. Design/methodology/approach: The OGP-VSM approach was developed by reviewing and integrating the environmental aspects of existing lean thinking tools and approaches. Findings: This research revealed the lack of practical integration between productive and environmental performance. Using OGP-VSM, managers can see that environmental practices have a direct impact on productivity. OGP-VSM allows a balance to be found between lean and green practices in order to achieve the simultaneous improvement of productivity and environmental performance. Practical implications: The proposed approach is applied to a case study in an automotive company in Spain and lays the groundwork for moving toward functional environmental sustainability in manufacturers. Originality/value: Companies are increasingly implementing environmentally focused practices. Pursuing environmentally friendly (green) performance poses several challenges, but it also affords opportunities to create new methodologies for generating a competitive advantage for manufacturing companies. There are a limited number of approaches to drawing together the elements and attributes that are essential for a holistic, practical and long-lasting improvement of environmental performance in the manufacturing sector.